Isosteviol Sodium Ameliorates Dextran Sodium Sulfate-Induced Chronic Colitis through the Regulation of Metabolic Profiling, Macrophage Polarization, and NF-κB Pathway. (27th January 2022) - Wang, Shanping; Huang, Jiandong; Tan, Keai Sinn; Deng, Liangjun; Liu, Fei; Tan, Wen
Abstract : Inflammatory bowel diseases (IBDs) constitute a group of chronic intestinal conditions prominently featuring deranged metabolism. Effective pharmacological treatments for IBDs are lacking. Isosteviol sodium (STV-Na) exhibits anti-inflammatory activity and may offer therapeutic benefits in chronic colitis. However, the associated mechanism remains unclear. This study is aimed at exploring the therapeutic effects of STV-Na against chronic colitis in terms of metabolic reprogramming and macrophage polarization. Results show that STV-Na attenuated weight loss and colonic pathological damage and restored the hematological and biochemical parameters in chronic colitis mice models. STV-Na also restored intestinal permeability by increasing the goblet cell numbers, which was accompanied by lowered plasma lipopolysaccharide and diamine oxidase levels. Metabolomic analysis highlighted 102 candidate biomarkers and 5 vital pathways that may be crucial in the potential pharmacological mechanism of STV-Na in regulating intestinal inflammation and oxidative stress. These pathways were glycerophospholipid metabolism, phenylalanine metabolism, phenylalanine, tyrosine and tryptophan biosynthesis, the pentose phosphate pathway, and phosphonate and phosphinate metabolism. Furthermore, STV-Na significantly decreased M1 macrophage polarization in the spleen and colon. The mRNA and protein levels of IL-1 β, TNF- α, and NF- κ B/p65 in colonic tissue from the colitis mice were decreased after the STV-Na treatment. Overall, STV-Na could alleviate chronic colitis by suppressing oxidative stress and inflammation levels, reprogramming the metabolic profile, inhibiting macrophage polarization, and suppressing the NF- κ B/p65 signaling pathway. STV-Na remains a promising candidate drug for treating IBDs.